#### Answer

fog(x) = 12

#### Work Step by Step

fog(x) = f(g(x))
f(5) = 12 and g(2) = 5
fog(x) = f(g(2)) = f(5) = 12

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

fog(x) = 12

fog(x) = f(g(x))
f(5) = 12 and g(2) = 5
fog(x) = f(g(2)) = f(5) = 12

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.